Scalable overlay multicast algorithm with high stability - Ye SHEN; Jing FENG; Zhan-feng WANG (Tongxin xuebao)
A new scalable overlay multicast algorithm with high stability(SOM-HS)was proposed.In SOM-HS algo-rithm,the node stability and the link weight factor were defined to ensure that the high stability nodes were located in the backbone network of multicast tree.In the hierarchica clustering configuration process,SOM-HS algorithm limits the degree of the nodes to ensure load balancing.The experimental results show that,the maximum delay with SOM-HS al-gorithm is minimum compared to the other existing algorithms in different multicast scales.